The Role of Extracurricular Dance in Increasing The Self-Confidence Of Lower-Class Students in MIN 1 Kediri - Zulaikhah, Rania Yulia; Saraswati, Ayu Ridho; Fitriani, Nisa (Proceeding International Conference on Education, 2024)
Arts education can help students develop their inner character, one of which is self-confidence. Dance is one of the artistic activities that can increase students' self-confidence through movement, rhythm, feeling, and skills. By dancing, students are guided to have the courage to appear in public, be responsible for their abilities, and be enthusiastic and confident. One of the activities that schools can provide to facilitate increasing students' self-confidence is extracurricular dance. This activity was carried out by lower-class students (grades 1 & 2 of elementary school) at MIN 1 Kediri. This research aims to analyze increasing self-confidence through dance extracurricular activities. This research is field research using a qualitative approach, where researchers collect data through observation, interviews, and study documents. The subjects of this research were teachers as dance extracurricular trainers and students who participated in dance extracurricular activities. The results of this research show that the dance extracurricular at MIN 1 Kediri helps increase the self-confidence of lower-class students.